(untitled) (Diametros, 2018)
The essay discusses the religious and ethical message of Shusaku Endo’s Silence. Briefly focusing first on the plot of the novel, the article proceeds to discuss the moral dilemma that is the core of the novel and asks whether the dilemma is symmetrical or incommensurable. Next, the essay analyzes the dilemma from the point of view of Max Scheler’s theory of the tragic. Finally, to highlight Rodrigues’s tragic situation, it discusses the notion of the hiddenness of God.